BUDAYA MAREN (GOTONG-ROYONG) SEBAGAI WUJUD TOLERANSI BERAGAMA MASYARAKAT MALUKU TENGGARA - Fenanlampir, Ancelina; Refo, Ignasius Samson Sudirman (LOGOS: JURNAL PENDIDIKAN KEAGAMAAN KATOLIK, 2022)
This research aims to explain the culture of "maren" (gotong royong), which is lived and practiced in the people of Southeast Maluku. In particular, it explains the contribution of "maren" culture to the realization of religious moderation. The research method used is qualitative research method. Data were collected through observation and interviews. Then all data were classified, arranged and then divided according to their types and used to answer research questions. From the results of this study it was found that "maren" culture can contribute to the realization of Pancasila values. With these values, "maren" culture can increase defense and development to achieve a change for the people of southeast Maluku, and can be used as a solution in overcoming the pressure to maintain the values of Pancasila.